Evolutionary game analysis of multi-agent behaviour decisions about sustainable agriculture - Xinlin Chen; Yun Teng; Guoming Du (International Journal of Climate Change Strategies and Management)
Purpose – Global climate change has become a challenge for the development of agriculture in the new stage. This study aims to promote the transformation and development of agriculture and the construction of climate adaptive agriculture, efforts should be made to promote farmers’ green production, realize the transformation of green agriculture and achieve the sustainability of agriculture in coping with climate change. Design/methodology/approach – In response to the characteristics of incomplete information and limited rationality among the government, farmers and consumers, an evolutionary game model was constructed among the three stakeholders to determine the conditions for stakeholders to obtain the optimal strategic combination to promote farmers’ green production behaviour (GB). Findings – A high reward and high punishment policy means that the reward given by government for GB reaches 2m yuan, and the fines paid by farmers to the government for non-green production behaviour reaches 2m yuan, which can effectively encourage farmers to adopt GB. The cost of green production for farmers should be controlled within 2m yuan, and the additional cost for consumers to purchase green agricultural products is less than 7m yuan, which is conducive to promoting farmers to adopt GB. Originality/value – For green production, only a small amount of research focuses on game evolution among the government, farmers and consumers, ignoring the important role of consumers. In this paper, an evolutionary game model among the government, farmers and consumers is constructed to promote the GB of farmers, which is conducive to green agriculture and curbing global climate warming.